Characteristics of undergraduate dental students in Japan: English competency and willingness to study abroad. (10th June 2016) - Takehara, Sachiko; Wright, FAC; Kawaguchi, Yoko; Ishida, Yuji; Morio, Ikuko; Tagami, Junji
Abstract : Objective: This study was conducted to acquire a deeper understanding of Japanese students' motivation to study abroad and to provide baseline information for nurturing globally‐minding dental students. Materials and Methods: Students from the first to the sixth year ( n = 332), at the Faculty of Dentistry, Tokyo Medical and Dental University, were invited to participate in the study and were asked to complete a self‐administered questionnaire, written in Japanese. Self‐reported English competency was assessed in four areas: reading; writing; speaking; and listening. Students were asked to score their competencies in these areas using a 10‐point visual analogue scale (VAS). Of the total eligible students, 312 (94%) participated. Results: The results of the study suggest that competency and confidence in the English language could be one of the biggest obstacles for students to study abroad. Students with an interest in studying abroad were highly motivated and studied English independently. Discussion and Conclusions: Japanese educational authorities and dental schools may need to consider a range of incentives and motivational strategies to nurture clinicians, educators and researchers who can function confidently in an increasingly borderless world. These could include increasing exposure to English language skills through mandatory lectures and seminars in English, increasing the range of inbound international students through student exchange programmes and encouraging students to develop and communicate with international colleagues. The Faculty of Dentistry at Tokyo Medical and Dental University has begun to increase exposure of students to English through the regular curriculum. Outcomes will be followed and evaluated.